The reporting syndrome, or when companies remember to manage information - García-Morales, Elisa (Anuario ThinkEPI, 2012)
Management reporting is a complex activity that requires multiple systems and information resources created for other purposes in the course of daily work. When companies have to write their management reports, they often suffer the problems of an inadequate information management system. Technological solutions by themselves do not respond to the needs, unless they are embedded in an information governance framework. Â